Design of experiments at bench tests of fuel supplying apparatus - E. V. Shendaleva; Kh. I. Khalimov (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article questions an experiment design of gas-turbine engine combustion unit at test bench. The relevance of statistical methods use and, particularly, experiment design for increase in reliability and safety of the aircraft equipment is undoubted. The article purpose is the methodological aspect development in uncertainty assessment of fuel consumption measurement in the test conditions at the semi-natural modeling stand. The experiment design use for combustion unit statistical model creation and uncertainty finding of fuel consumption measurement is offered